2021
DOI: 10.1111/fcp.12695
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in DMARD‐treated patients with inflammatory rheumatic diseases: Insights from an analysis of the World Health Organization pharmacovigilance database

Abstract: Background To determine whether the use of disease‐modifying antirheumatic drugs (DMARDs) is linked to the risk of COVID‐19 among patients with inflammatory rheumatic diseases (IRDs). Methods We performed a disproportionality analysis of the World Health Organization pharmacovigilance database between January 1, 2020, and June 10, 2020. The frequency of COVID‐19 reports for all DMARD classes identified was compared with that for all other reports for all other drugs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
5
0
3
Order By: Relevance
“…Согласно данным C19-GRA, в период пандемии COVID-19 (с марта 2020 г. по апрель 2021 г) РТМ и иЯК показали статистически значимую связь с тяжелым течением COVID-19; для препаратов из группы ирИЛ-6 такая связь не выявлена [21]. В докладе Фармаконадзора ВОЗ у пациентов с РА отмечалась обратная связь терапии ирИЛ-6 (тоцилизумабом) с тяжестью течения COVID-19, что подтверждает высокую безопасность применения таких препаратов у пациентов с ИВРЗ [12].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Согласно данным C19-GRA, в период пандемии COVID-19 (с марта 2020 г. по апрель 2021 г) РТМ и иЯК показали статистически значимую связь с тяжелым течением COVID-19; для препаратов из группы ирИЛ-6 такая связь не выявлена [21]. В докладе Фармаконадзора ВОЗ у пациентов с РА отмечалась обратная связь терапии ирИЛ-6 (тоцилизумабом) с тяжестью течения COVID-19, что подтверждает высокую безопасность применения таких препаратов у пациентов с ИВРЗ [12].…”
Section: Discussionunclassified
“…По результатам отчета Фармаконадзора Всемирной организации здравоохранения (ВОЗ), показан потенциально лучший профиль безопасности для ирИЛ6 и иЯК [12]. По данным ряда исследований, пациенты, получавшие ГИБП, особенно иФНО-α, реже нуждались в госпитализации [5].…”
Section: Introductionunclassified
“…Patients with rheumatic disease on DMARDs like le unomide might have a protective role by prevention of cytokine storm from severe COVID19 [23]. Other studies the WHO pharmacovigilance data suggestive of more frequent presentation of COVID-19 is in ammatory rheumatic disease (IRD) patients on TNF inhibitors [24]. In accordance with our report, during the study period, a nationwide cohort study demonstrated that patients with rheumatic diseases treated with a high dose of corticosteroid associated with adverse outcome of COVID-19, however patients on DMARDs were at lower risk in disease outcome [25].…”
Section: Discussionmentioning
confidence: 99%
“…In VeroE6 P‐glycoprotein knockout cells, nirmatrelvir has been shown to potently inhibit the replication of SARS‐CoV‐2 viruses, suggesting that nirmatrelvir is a substrate of P‐glycoprotein, 120 although the involvement of P‐glycoprotein has not been fully confirmed 121 . In contrast to molnupiravir and nirmatrelvir, remdesivir has been identified to be a substrate of multiple transporters including BSEP, MATE1, MRP4, NTCP, OATP1B1/1B3, and OCT1 122,123 . These transporters are abundantly expressed in the liver.…”
Section: Metabolism and Active Transportmentioning
confidence: 99%